Gentiana betongensis (Gentianaceae), a new species from tropical montane sphagnum bog in Peninsular Thailand - Wai, Jarearnsak Sae (Phytotaxa, 2024)
Gentiana betongensis is described as a new species from Thailand. It was discovered in tropical montane sphagnum bog of the High Plateau in Betong District, Yala Province near the Thai-Malay Border. The new species is morphologically most similar to G. malayana in having erect, simple or few-branched stems, but differs markedly in having smaller flowers, triangular-ovate, acute corolla lobes, and long, recurved and coiled stigma lobes. This paper provides morphological description, illustration, photographs, distribution map, ecological data, reproductive biology, DNA barcode sequence, vernacular name, conservation status, a key to the species of Gentiana in Thailand, Peninsular Malaysia and Borneo, and a special note on conservation perspectives.